2008
DOI: 10.1364/ao.47.000644
|View full text |Cite
|
Sign up to set email alerts
|

Point shifting in the optical testing of fast aspheric concave surfaces by a cylindrical screen

Abstract: A method for increasing the precision and sensitivity of the quantitative evaluation of fast aspheric surfaces through the null screen method is presented. This consists of applying small displacements to the cylindrical null screen along the optical axis. These movements allow a scan of the image spots over zones that with the analysis of a single image are more difficult to evaluate. The precision of the test is increased due to a greater density of sampling reducing the numerical errors during the integrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The final stepstone for convenient low-uncertainty evaluation was the introduction of the phase-shifting technique, created for interferometry in the 1970s and immediately adopted for fringe projection after sufficient digital storage and processing means became available [183][184][185]. Surprisingly, phase shifting has spread to deflectometry only around the turn of the millennium [7,158,[186][187][188][189][190][191][192] one reason may be that convenient flat-screen monitors for displaying modulated patterns were starting to become available at that time. As a result, moiré techniques are now largely obsolete in DM, and can in hindsight be interpreted as a complicated way (but necessary at the time) to reduce uncertainties.…”
Section: Historical Overviewmentioning
confidence: 99%
“…The final stepstone for convenient low-uncertainty evaluation was the introduction of the phase-shifting technique, created for interferometry in the 1970s and immediately adopted for fringe projection after sufficient digital storage and processing means became available [183][184][185]. Surprisingly, phase shifting has spread to deflectometry only around the turn of the millennium [7,158,[186][187][188][189][190][191][192] one reason may be that convenient flat-screen monitors for displaying modulated patterns were starting to become available at that time. As a result, moiré techniques are now largely obsolete in DM, and can in hindsight be interpreted as a complicated way (but necessary at the time) to reduce uncertainties.…”
Section: Historical Overviewmentioning
confidence: 99%
“…Second, the number of evaluation points is also increased, as is the evaluation time. Finally, in [33] it is shown that with a higher density of points the numerical errors introduced by the integration algorithm are reduced. The density, however, cannot be increased indefinitely because of the resolution of the laser printer and of the CCD camera.…”
Section: Research Articlementioning
confidence: 99%
“…The density, however, cannot be increased indefinitely because of the resolution of the laser printer and of the CCD camera. However, it is possible to increase the density of points of evaluation by considering the point shifting procedure by using a dynamic null-screen [33], this nullscreen could be implemented on an LCD monitor [34] and one can use chromatic [35] and/or monochromatic arrays of points [36].…”
Section: Research Articlementioning
confidence: 99%
“…An important problem in the test with a null screen is that the integration method accumulates important numerical errors along the different selected integration paths. It is well known (Moreno-Oliva et al, 2008a) that a bound to the so called truncation error can be written as…”
Section: Surface Shape Evaluationmentioning
confidence: 99%
“…This implies more spots in the design of the null screen; there is, however, a physical limit on the number of spots; if the spot density is too large,the spot images can overlap because of defocus, aberrations or because of diffraction. A method to increase the number of points, thus reducing the average separation between them, is to use the so called point shifting method (Moreno-Oliva et al, 2008a;Moreno-Oliva et al, 2008b). The basic idea is to acquire a total of m pictures, each with different null screen arrangement and containing n spots on the image; the spots will be shifted from their positions in other pictures, making a total of m×n evaluation points, with an average separation of…”
Section: Surface Shape Evaluationmentioning
confidence: 99%